Strategi Badan Narkotika Nasional Kota dalam Memberantas Peredaran Narkoba di Tanjungpinang - effendi, desrian; Asparianto, Syahrizal (STISIPOL Raja Haji, 2020)
National Narcotic Agency (NNA) is a government agency Non-Ministry in Indonesia, who has government responsibility for minimizing the abuse of controlled substances through preventation an law enforcement measures directed primarily at illegal drug abuse and drug trafficking preventing of psikotoprika, prekusor, an addictive’s other. This research aims to know about strategic of National Narcotic Agency (NNA) to abusing drugs trafficking in Tanjungpinang City. In this study researchers using descriptive qualitative methods that produce descriptive data in the form of words written or spoken from the people and behavior observed. The technique used in this research is the interview, with the research informants is 6 people. Data analysis used is by collecting data, processing data, and giving conclusion and verification. The results of this study found that National Narcotic Agency (NNA) using two strategic. First, they doing demand reduction and the second strategic is minimizing the supply of drugs. To reach this strategic, National Narcotic Agency (NNA) of Tanjungpinang City doing social mapping in district and subdistrict with has a collaboration with community leader, local people, stake holder and others to get information about the drug-prone area. In the other hand, National Narcotic Agency (NNA) of Tanjungpinang City using horizontal integration strategic, to doing monitoring and controlling drugs trafficking case. in order to doing they responsibly, National Narcotic Agency (NNA) of Tanjungpinang City has stresngths and weaknesses. It can looking by infrastructure, transportation, and ability of manpower in structure of National Narcotic Agency (NNA) Tanjungpinang. But, budget is a threat of National Narcotic Agency (NNA) doing they duties. it because the budget for abusing drugs trafficking is decreasing every year. That’s making they duties be deferred. The influence of friend, treachery and trap trespass of others people, politic regulation of regional regulation about permitted of the nightclub in Tanjungpinang given the contribution of drugs trafficking still exist until now. According the result of study from primer and secunder data, researches find out that National Narcotic Agency (NNA) has a plan to knowing about the strengths, weaknesses, oppurtunity, and threats. That’s is one of the alternative strategic of National Narcotic Agency (NNA) to stopping the generation of drugs distributor in case to abusing drugs trafficking. Badan Narkotika Nasional (BNN) merupakan Sebuah Lembaga Pemerintah Non-Kementerian (LPNK) Indonesia yang bertugas melaksanakan tugas pemerintahan di bidang pencegahan, pemberantasan terhadap penyalahgunaan, dan peredaran gelap psikotropika, prekursor, dan bahan adiktif lainnya Lembaga yang bertujuan untuk memberantas peredaran gelap narkoba. Penelitian ini bertujuan untuk mengetahui bagaimana strategi Badan Narkotika NasionaL (BNN-K) dalam memberantas peredaran narkoba di kota Tanjungpinang. Dalam penelitian ini peneliti menggunakan metode deskriptif kualitatif yang menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari orang-orang dan perilaku yang diamati. Teknik yang digunakan dalam penelitian ini adalah wawancara, dengan informan penelitian sebanyak 6 orang, Analisa data yang digunakan adalah dengan cara mengumpulkan data, mengolah data, serta pemberian kesimpulan dan verifikasi. Hasil dari penelitian ini ditemukan bahwa dalam memberantas perederan narkoba, Badan Narkotika Nasional (BNN) menggunakan dua yaitu Strategi meliputi strategi pengurangan terhadap permintaan dan yang kedua Strategi pengurangan terhadap Pasokan. Untuk mendukung Strategi itu maka BNN kota Tanjungpinang melakukan Pemetaan Jaringan di Kecamatan dan Kelurahan yang dilakukan dengan cara bekerja sama baik dengan tokoh masyarakat, warga sekitar maupun stakeholder lainnya, untuk mendapatkan informasi tentang Tempat/Lokasi Rawan Narkoba. Selanjutnya, BNN kota Tanjungpinang juga menggunakan strategi integrasi horizontal dalam meningkatkan pengawasan serta kendali terkait peredaran narkoba. Dalam melakanakan tugasnya, Badan Narkotika Nasional kota Tanjungpinang memiliki kekuatan dan kelemahan. Hal tersebut dapat dilihat dari sarana dan prasarana, transportasi darat, serta kemampuan Sumber Daya manusia di BNN Kota Tanjungpinang tersebut. Tetapi selain itu, Anggaran menjadi salah satu hambatan dalam menjalankan tugas. Hal ini disebabkan anggaran untuk pemberantasan menurun setiap tahun sehingga beberapa kasus akan ditangguh sementara. Meskipun begitu pengaruh teman, paksaan dan jebakan teman, hasil Regulasi politik melalui perda yang mengizinkan pengoperasian hiburan malam di Tanjungpinang menyebabkan peredaran narkoba masih aktif hingga sekarang. Berdasarkan hasil penelitian dari data primer dan sekunder yang penulis dapatkan diketahui kekuatan, kelemahan, peluang dan ancaman memiki salah satu alterlatif strategi yang disarankan yaitu Strategi pemusnahan terhadap pengedar agar tidak memiliki penerus terhadap peredaran narkoba.